1993
DOI: 10.1007/bf00186247
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical study of afferent projections to the supramammillary nucleus of the rat

Abstract: We examined the regions projecting to the supramammillary nucleus of the rat with retrograde transport of WGA-HRP and WGA, and anterograde transport of Phaseolus vulgaris leucoagglutinin. The supramammillary nucleus receives major descending afferents from the infralimbic cortex, the dorsal peduncular cortex, the nucleus of the diagonal band of Broca, the medial and lateral preoptic nuclei, bilaterally. The major ascending afferents come from the pars compacta of the nucleus centralis superior, the ventral teg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 48 publications
7
41
1
Order By: Relevance
“…Procaine in the mSuM itself reduced both the frequency and amplitude of theta. A transduction role for the mSuM of brainstem impulses bound for the medial septum is consistent with tracing studies that have identified projections to the mSuM from the RPO (Vertes & Martin, 1988) and other brainstem structures (Hayakawa, Ito, & Zyo, 1993) and from the mSuM to the medial septum via the median forebrain bundle (Borhegyi, Magloczky, Acsady, & Freund, 1998;Shepard, Mihailoff, & German, 1988;Vertes, 1988Vertes, , 1992.…”
supporting
confidence: 85%
“…Procaine in the mSuM itself reduced both the frequency and amplitude of theta. A transduction role for the mSuM of brainstem impulses bound for the medial septum is consistent with tracing studies that have identified projections to the mSuM from the RPO (Vertes & Martin, 1988) and other brainstem structures (Hayakawa, Ito, & Zyo, 1993) and from the mSuM to the medial septum via the median forebrain bundle (Borhegyi, Magloczky, Acsady, & Freund, 1998;Shepard, Mihailoff, & German, 1988;Vertes, 1988Vertes, , 1992.…”
supporting
confidence: 85%
“…There are reciprocal connections between the SUM and the preoptic area, the diagonal band nucleus, and the laterodorsal tegmental nucleus at the light microscopic level (Swanson 1982;Satoh and Fibiger 1986;Vertes 1992;Hayakawa et al 1993). The present study suggests that they exist at the ultrastructural level, except in the case of the laterodorsal tegmental nucleus.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings agree with theirs concerning the morphology of terminals from the infralimbic cortex. Our previous study using anter0grade tracing with Phaseolus vulgaris leucoagglutinin (Hayakawa et al 1993) showed that afferent projections from the infralimbic cortex were confined to the ventral region of the SUM. Infralimbic cortical neurons may contact dopaminergic neurons in the SUM as well as in the ventral tegmental area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SUM projects to the cingulate cortex, the infralimbic cortex, the entorhinal cortex, the septal nuclei, the hippocampus, the preoptic area, and the midbrain tegmentum (Wyss et al, 1979;Veazey et al, 1982;Haglund et al, 1984;Vertes, 1992). The major afferent fibers come from the infralimbic cortex, the septal nuclei, the preoptic area, and the laterodorsal tegmental nucleus (Swanson, 1976;Swanson and Cowan, 1979;Sesack et al, 1989;Satoh and Fibiger, 1986;Hurley et al, 1991;Hayakawa et al, 1993). Many cholinergic fibers are present in the SUM (Ruggiero et al, 1990).…”
mentioning
confidence: 97%